Ginsenoside CK and retinol on UVA-induced photoaging exert the synergistic effect through antioxidant and antiapoptotic mechanisms - Jingyin Zhang; Zhuojun Li; Xiaoping Song; Panpan Cai; Qingchao Liu (Scientific Reports)
Abstract Retinol and retinoids can effectively intervene skin aging process, but usually induce skin intolerance. In this study, we aimed to determine the synergistic anti-aging effects of retinol and two retinol derivatives-hydroxypinacolone retinoate (HPR) and retinol palmitate (VAPA) combined with ginsenoside CK in terms of preventing and treating the UVA radiation-induced skin aging. We found that the combination formulation of retinol and ginsenoside CK alleviated the inhibition of photoaging proliferation of HaCaT cells caused by UVA, and reduced the proportion of senescence. Additionally, the combination of retinol, HPR, VAPA with ginsenoside CK significantly down-regulated the expression of P53 and P21, up-regulated P63 in UVA irradiated cells, and had potential anti-apoptotic activity. Ginsenoside CK intervention also inhibited the degradation of collagen and elastin by reducing the expression of matrix metalloproteinases, and significantly alleviated oxidative stress. Further transcriptomic and molecular docking studies suggested that ginsenoside CK may play an anti-photoaging role by binding to the active pocket of AKR1C1 and AKR1C2 proteins. Zebrafish experiment showed that retinol combined with ginsenoside CK had the effect of reducing skin toxicity. In conclusion, our results show that retinol, HPR and VAPA combined with ginsenoside CK have good anti-aging and irritation-reducing effects in vitro and in vivo.